Pengaruh Pajak Penjualan PPN Dan PPnBM Terhadap Laba Rugi Fiskal Pada UD Gemah Ripah - Viola Ardhana; Khasanah Sahara; Imarotus Suaidah (Intellektika : Jurnal Ilmiah Mahasiswa, 2023)
Taxes are a very important source for a sector of state revenue. To further increase revenue in the tax sector, several improvements have been made. In this research, the researcher tries to discuss the above problems related to "The Influence of Sales Tax VAT and PPnBM on Commercial Profits and Fiscal Profits of UD Gemah Ripah". The research model used in this research is associative research, namely to look at the influence of Fiscal Profit on VAT and PPnBM. This research was carried out at UD Gemah Ripah which is located on Jl. Padang Padi No.13, Kaliombo, Kec. Kota, Kediri City, East Java 64126. After conducting tests and calculations, it was found that UD Gemah Ripah's income tax in 2020 was IDR. 484,044,806.88, in 2021 it is IDR. 1,005,309,943.19, and in 2022 it will be IDR. 563,112,212.29. According to the data obtained, it was also found that PPn and PPnBM were not included in the requirements for calculating corporate PPh from UD Gemah Ripah, corporate PPh from UD Gemah Ripah only calculated from turnover and net profit before PPh. And also from several of these calculations, it was found that the PPn and PPnBM that must be paid are not necessarily directly proportional to the net profit of UD Gemah Ripah.